Retail Trade in the Sverdlovsk Region in 1951-1958 - V. N. Mamyachenkov; E. S. Kulikova (Научный диалог, 2020)
The article is devoted to a rather relevant, but still little developed topic in regional historiography. The basis for the study was largely unpublished materials from three regional archives. It is stated that trade is the basis of the development of the economy of any state. It is stated that the purpose of this article was to study the state of retail trade in the Middle Urals (Sverdlovsk Region) in one of the interesting periods in the history of the former USSR - the fifth and sixth (incomplete) five-year periods (1951-1958). It is declared that it was during the mentioned period that the country began to gradually move away from the difficult legacy of Stalin's totalitarianism, very significant economic projects were being implemented, and the reform of the management of the national economy was launched. There were impressive scientific achievements, primarily in the military and military space fields. It is argued that the beginning of the study period in the trading sector of the Middle Urals did not inspire much optimism. The thesis is put forward that, as the Soviet economy developed, the situation in the trade sphere also gradually changed for the better. It is noted that the assortment of goods that Soviet trade had in the period under study clearly lagged behind modern requirements. It is concluded that the period under study was a step forward in the development of the trading sphere of the Middle Urals, although it was still very far from meeting its civilized standards.